Analisis Studi Kasus: Observasi Respons Fisik, Pemicu Social Anxiety, dan Kajian Furnitur Publik Eksisting di Ruang Publik - Sutanto, Dharma Adhi; Hairunnas, Hairunnas; Sujatmiko, Guguh (SPACEPRO: Product Design Jurnal, 2025)
This study aims to analyze the physical responses associated with social anxiety, identify its underlying factors, and evaluate existing public furniture in Surabaya's public spaces. Utilizing a case study and observational methodology, data were collected through direct field observations and surveys administered to public space users. The research employed both qualitative and quantitative analysis to comprehensively understand the interplay between environmental conditions and the physical manifestations of social anxiety. Findings indicate that behaviors such as increased mobile phone usage, grounding techniques, and fidgeting are significant physical responses when individuals encounter ambiguous or crowded public environments. Additionally, the evaluation of current public furniture revealed that existing designs do not adequately address the needs of users experiencing social anxiety, highlighting a critical opportunity for innovative design interventions. In conclusion, enhancing the design of public furniture to be more responsive to the emotional and physical needs of users can serve as an effective strategy in reducing social anxiety levels and improving the overall quality of urban public experiences.